Nodular Pulmonary Amyloidosis: A Manifestation of Sjögren’s Syndrome - Gustavo Adolfo Gómez Correa; Jovani Osorno Serna; Manuel Felipe Cáceres Acosta; Juan David Cáceres González; Jaime Andrés Calle Ramirez; Juan Paulo Sandoval Mesa; Miguel Ignacio Roldán Pérez (Case Reports in Pulmonology)
Case Description. A 72-year-old woman with primary Sjögren Syndrome (SS) was diagnosed during an inpatient hospital stay with dry symptoms. The patient had respiratory and constitutional symptoms, requiring a pulmonary imaging evaluation by high-resolution computed tomography (HRCT) of the thorax. Clinical Findings. Multiple cavitary pulmonary nodules, halo sign, and focal areas of ground-glass opacity with predominance in both bases were found in the images. Complementary studies were done where a neoplastic focus was ruled out. The diagnosis of nodular pulmonary amyloidosis was confirmed with a pulmonary biopsy performed by videothoracoscopy for histopathological study, which reported the formation of nodules in the parenchyma with amyloid deposits and positive immunohistochemical markers for CD3, CD20, and CD38 lymphocytic infiltration. Treatment and Outcome. Initial inpatient management with intravenous cyclophosphamide and methylprednisolone was given. Subsequent outpatient management was given with high dose glucocorticoids. Clinical Relevance. We presented a case of nodular pulmonary amyloidosis in a female patient with primary SS, which is a rare pulmonary manifestation of this syndrome.